Kinematic analysis of subtalar eversion during gait in women with fibromyalgia. (August 2016) - Silva, Ana Paula; Chagas, Daniel das Virgens; Cavaliere, Maria Lúcia; Pinto, Sérgio; de Oliveira Barbosa, José Silvio; Batista, Luiz Alberto
Abstract: Objective: To analyse the subtalar eversion range of motion during walking in women with fibromyalgia. Method: Twenty women diagnosed with fibromyalgia were directed to walk barefoot at comfortable and self-paced speed on a 7m walkway. Subtalar eversion range of motion was measured using the difference between the maximum and minimum values of subtalar eversion in stance phase. A range of motion between 4°–6° was considered as reference values for subtalar eversion during gait. Descriptive statistics were performed. Results: In both right and left lower limb analysis of subtalar eversion range of motion, five women showed joint hypomobility, and twelve showed hypermobility. Only one patient performed unaltered subtalar eversion range of motion in both lower limbs. Both joints expressed high variability, and there were no significant differences between the right and left sides. Conclusions: The findings suggest that biomechanical function of the subtalar joint eversion during the loading response phase of gait in women with fibromyalgia, by excessive rigidity or complacency joint, tends to be impaired. This finding suggests that the indication of walking as an auxiliary strategy in the treatment of women with fibromyalgia should be preceded by thorough examination of the mechanical conditions of the subtalar joint of the patient.